Reducing effect of saikosaponin A, an active ingredient of Bupleurum falcatum, on alcohol self-administration in rats: Possible involvement of the GABAB receptor. (16th May 2016) - Maccioni, Paola; Lorrai, Irene; Carai, Mauro A.M.; Riva, Antonella; Morazzoni, Paolo; Mugnaini, Claudia; Corelli, Federico; Gessa, Gian Luigi; Colombo, Giancarlo
Highlights: Saikosaponin A is a major ingredient of the medicinal herb, Bupleurum falcatum . Saikosaponin A reduced oral alcohol self-administration in alcohol-preferring rats. The effect of saikosaponin A was mediated, at least in part, by the GABAB receptor. These results extend to alcohol recent literature data on morphine and cocaine. Abstract: Recent studies demonstrated that treatment with saikosaponin A (SSA) – an active ingredient of the medicinal herb, Bupleurum falcatum L . – selectively suppressed, likely via a GABAB receptor-mediated mechanism, intravenous self-administration of morphine and cocaine in rats [Yoon et al., 2012; 2013]. The present study was designed to investigate whether the capacity of SSA to suppress morphine and cocaine self-administration extends to oral alcohol self-administration. To this end, selectively bred Sardinian alcohol-preferring (sP) rats were trained to lever-respond on a Fixed Ratio (FR) 4 (FR4) schedule of reinforcement for alcohol (15%, v/v) in daily 30-min sessions. Once responding had stabilized, rats were tested under the FR4 (measure of alcohol reinforcing properties) and Progressive Ratio (PR; measure of alcohol motivational properties) schedules of reinforcement. The possible involvement of the GABAB receptor system was investigated testing the effect of (a) pretreatment with the GABAB receptor antagonist, SCH50911, and (b) combined treatment with the positive allosteric modulator of the GABAB receptor, GS39783. Treatment with SSA (0, 0.25, 0.5, and 1 mg/kg, i.p.) markedly reduced lever-responding for alcohol, amount of self-administered alcohol, and breakpoint for alcohol (defined as the lowest response requirement not achieved in the PR experiment). Pretreatment with 2 mg/kg SCH50911 (i.p.) resulted in a partial blockade of the reducing effect of 0.5 mg/kg SSA on lever-responding for alcohol and amount of self-administered alcohol. Combination of per se ineffective doses of GS39783 (5 mg/kg, i.g.) and SSA (0.1 mg/kg, i.p.) reduced lever-responding for alcohol and amount of self-administered alcohol. These results (a) extend to alcohol self-administration the capacity of SSA to suppress morphine and cocaine self-administration in rats and (b) suggest that the GABAB receptor system is likely part of the neural substrate underlying the reducing effect of SSA on alcohol self-administration.